PERGESERAN PARADIGMA TAFSIR ALA LINGUIS: (Memamahi Ide Pembaruan dan Model Penafsiran M. Syahrur) - John Supriyanto (Al-Dirayah, 2018)
This paper tries to explore one of the children's understanding of the knowledge of the Qur'an and tafsir. Muhammad Syahrur ad-Dayyub, a linguist and based on civil engineering, offers a new approach to understanding the Qur'an. Syahrur's ideas about the Qur'an which he published in "Al-Kitab wa al-Qur'an: Qira'ah Mu’ashirah" were offered as the most ideal contemporary reading method in accordance with the social dynamics nowadays. In this case, Shahrur wants as if the Qur'an is a holy book that has just been revealed. The offer has deconstructed and reconstructed the Qur'anic knowledge and interpretations which have been "considered" established. Some figures argue that Syahur ideas as something completely new so that they need to be positively appreciated in the creative discourse of reading religious papers. However, some figures also respond to their thoughts with scorn, even blasphemy.